Bidirectional relationship between olfaction and Parkinson’s disease - Jonggeol Jeffrey Kim; Sara Bandres-Ciga; Karl Heilbron; 23andMe Research Team; Cornelis Blauwendraat; Alastair J. Noyce (npj Parkinson's Disease)
Abstract Hyposmia (decreased smell function) is a common early symptom of Parkinson’s disease (PD). The shared genetic architecture between hyposmia and PD is unknown. We leveraged genome-wide association study (GWAS) results for self-assessment of ‘ability to smell’ and PD diagnosis to determine shared genetic architecture between the two traits. Linkage disequilibrium score (LDSC) regression found that the sense of smell negatively correlated at a genome-wide level with PD. Local Analysis of [co]Variant Association (LAVA) found negative correlations in four genetic loci near GBA1, ANAPC4, SNCA, and MAPT, indicating shared genetic liability only within a subset of prominent PD risk genes. Using Mendelian randomization, we found evidence for a strong causal relationship between PD and liability towards poorer sense of smell, but weaker evidence for the reverse direction. This work highlights the heritability of olfactory function and its relationship with PD heritability and provides further insight into the association between PD and hyposmia.